1976
DOI: 10.1007/bf02532578
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between erucic acid and myocardial changes in male rats

Abstract: The back and belly fat of pigs fed a diet containing 20% by wt rapeseed oil (22% erucic acid) for 16 weeks was rendered into oil. This rendered pig fat, which contained 5.6% erucic acid, was fed to male rats in three separate experiments at 20% by wt of the diet for 16 weeks. In experiment I rendered pig fat was compared only to Brassica campestris var. Span rapeseed oil containing 4.8% erucic acid. In experiments II and III, rendered pig fat was compared to commercial lard containing 0.2% docosenoic acid, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…Interestingly, the Chester Beatty (Hooded) rat, which also absorbs fat via the portal system, does not show evidence of myocardial damage when fed rapeseed oils (Hulan et al, 1977a). These results tend to support our previous hypothesis (Hulan et al, 1976) that erucic acid per se is not the sole causative agent of myocardial damage as postulated by Abdellatif and Vies (1973). The myocardial damage observed in the R-500 fed chickens in the current studies is likely related to the fatty acid imbalance of the oil coupled with its extremely high 22:1 content.…”
Section: C Q Csupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the Chester Beatty (Hooded) rat, which also absorbs fat via the portal system, does not show evidence of myocardial damage when fed rapeseed oils (Hulan et al, 1977a). These results tend to support our previous hypothesis (Hulan et al, 1976) that erucic acid per se is not the sole causative agent of myocardial damage as postulated by Abdellatif and Vies (1973). The myocardial damage observed in the R-500 fed chickens in the current studies is likely related to the fatty acid imbalance of the oil coupled with its extremely high 22:1 content.…”
Section: C Q Csupporting
confidence: 88%
“…Interestingly, the level of 22:1 in cardiac lipids in chickens fed control, soybean oil, Tower, or Candle RSO was not significantly different. The significantly lower concentration of 18:1 in the cardiac lipids of chickens fed the diet containing Candle RSO (54.46% 18:1) compared to that of chickens fed the control diet (19.98% 18:1) or Tower RSO (61.98% 18:1) should be noted since tissue lipids usually reflect the fatty acid composition (type and proportion) of the diet fed (Hulan <>£«/., 1976(Hulan <>£«/., , 1977c.…”
Section: Resultsmentioning
confidence: 96%
“…However, when rats were fed on a diet containing 9.2Cal% erucic acid for 2 weeks, only minor fatty infiltration of the heart and skeletal muscles was observed (15). Erucic acid having no significant influence was also reported in myocardial lesions when rats were fed for 16 weeks on commercial lard to which 5.4% erucic acid was added (16). Erucic acid in winged bean seed oil was found only at a level of 0.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researches on fat metabolism have come to suggest some possible adverse effects of erucic acid in the diet (14)(15)(16). However, when rats were fed on a diet containing 9.2Cal% erucic acid for 2 weeks, only minor fatty infiltration of the heart and skeletal muscles was observed (15).…”
Section: Discussionmentioning
confidence: 99%
“…1835. et al, 1977aKramer et al, 1979aKramer et al, , 1973, peanut oil (Ackman, 1974, Cluzan et al, 1979Rocquelin and Cluzan, 1968;Vies et al, 1979), soybean oil (Hulan et al, 1977b;Kramer et al, 1979b;McCutcheon et al, 1976;Slinger, 1977), sunflower oil (Vies, 1978;Vies et al, 1976Vies et al, , 1978, safflower oil (Kramer et al, 1975;McCutcheon et al, 1976), lard (Hulan et al, 1976), and lard/corn oil mixtures (Beare-Rogers and Nera, 1977;Beare-Rogers et al, 1979, 1974. These findings indicated that factors other than, or in addition to, erucic acid were responsible for the increased incidence of cardiac lesions.…”
Section: Introductionmentioning
confidence: 67%